S10.3 Genetical and phenotypical findings of childhood-onset systemic lupus erythematosus. (27th September 2022) - Morán Álvarez, P; Passarelli, C; Messia, V; Pardeo, M; Marasco, E; Insalaco, A; De Benedetti, F; De Benedetti, F; Bracaglia, C
Abstract : Purpose to identify the presence of variants in gene related to monogenic lupus and their relationship with clinical manifestations in childhood-onset systemic lupus erythematosus (cSLE) or lupus-like phenotype. Methods: a descriptive, observational, cross-sectional study was carried out in children with a diagnosis of cSLE or with lupus-like. The genetic analysis (Sanger/Clinical Exome Sequencing) was performed from isolated DNA obtained from blood sample. Results: Forty-two children were included in the study. The genetic analysis detected at least one variant in 11 (26.1%) children, 5 (45.4%) with cSLE and 6 (54.5%) with lupus-like phenotype. Of those who carry a genetic variant, the median age at disease onset was 11 years (range: 2–16) and 72.7% were female. Most of them were Caucasians (72.7%). Four (36.3%) and 3 (27.2%) out of 11 patients had a positive family history and/or a personal history for autoimmune diseases, respectively. Regarding the clinical manifestations at onset, musculoskeletal was the most frequent (8 patients, 72.7%), followed by hematological (6 patients, 54.5%), cutaneous (6 patients, 54.5%), constitutional with fever (5 patients, 45.45%), neurological (4 patients, 36.3%), renal (3 patients, 27.2%), cardiac (3 patients, 27.2%) and pulmonary (2 patients, 18.1%) manifestations. Related to immunological parameters, 10 (90.9%) were ANA positive, 5 (45.4%) anti-dsDNA, 4 (36.3%) ENA and 2 (18.1%) were antiphospholipid antibodies and lupus anticoagulant positive. Both C3 and C4 were low in 5 (45.4%) children and isolated C3 levels were low in 4 (36.3%) patients. Among the variants, we found that only two patients who carry a TREX variant showed normal C3 and C4 levels; one of them presented with lupus pernio as reported in literature. The same RNASEH2B (c.868G>A) variant was identified in two siblings with similar phenotype. The patient who carried the SHOC2 variant presented polyarthritis and serositis, while the patient with the TNFRSF13B variant onset with a glomerulonephritis. Those manifestations have already been described related to these gene variants. Clinical manifestations and variants are detailed in Table 1 . Conclusions: Around 25% pediatric patients with cSLE or lupus-like phenotype in our cohort showed at least one variant in gene related to monogenic-lupus and some of them had a phenotype similar to those already described. The evidence of these variants may suggest the genetics potential contribution to the cSLE pathogenesis. Further studies in larger cohorts are necessary to confirm these data.